Vitamin D levels and cardiometabolic risk factors in Portuguese adolescents. (1st October 2016) - Cabral, Maria; Araújo, Joana; Teixeira, Joana; Barros, Henrique; Martins, Sandra; Guimarães, João Tiago; Lopes, Carla; Ramos, Elisabete
Abstract: Background: Growing evidence suggests a possible association between low vitamin D levels and increased cardiovascular risk. However, research regarding the period of adolescence is scarce. We aimed to evaluate the association of vitamin D, intake and serum 25(OH)D levels, with cardiometabolic risk factors in 13-year-old adolescents. Methods: We conducted a cross-sectional analysis of 1033 adolescents evaluated at 13 years oldas part of the population-based cohort EPITeen. Vitamin D intake was assessed by a food frequency questionnaire. Serum 25(OH)D levels were assessed for a subsample of 514 participants. Metabolic syndrome (MetS) features were defined according to the National Cholesterol Education Program Adult Treatment Panel III definition modified for age. Logistic regression was fitted to estimate the association between vitamin D status and cardiometabolic risk factors, adjusting for sex, parental education, BMI, physical activity and season. Results: Mean (SD) vitamin D levels, 4.61 (2.50) μg for intake and 16.52 (5.72) ng/mL for serum, were below the recommendations. The prevalence of MetS was 13.2%. Total cholesterol and LDL levels significantly decreased with 25(OH)D serum increase. After adjustment, no association was found between vitamin D levels and MetS. Regarding MetS features, an increased odds of high BMI was observed for those with a lower intake (OR 1.87 95% CI 1.04–3.35). Conclusions: Although a significant increase in total and LDL cholesterol was observed for lower 25(OH)D levels, and an increased odds of high BMI was observed for those with a lower vitamin D intake, no significant association was observed between vitamin D levels and metabolic syndrome.